OXYGEN ISOTOPE FRACTIONATION IN FERRIC OXIDE-WATER SYSTEMS: LOW TEMPERATURE SYNTHESIS - Bao H.; Koch P.L. (My University, 1999)
The magnitude and temperature-sensitivity of oxygen isotope fractionation in ferric oxide-water systems remain uncertain. In this study, three different synthetic methods are used to investigate the temperature dependence of the fractionation between water and hematite, akaganeite, and goethite at near-surface temperatures. Our results reveal two similarities among these ferric oxide-water systems. First, the fractionation of oxygen isotopes between water and ferric oxide is small (i.e., ferric oxide-water fractionation factors [α] are very close to 1.000). Second, these α values are relatively insensitive to change in temperature (T). Hematite-water has a slightly higher α value and a greater temperature sensitivity than goethite-water at surface temperatures. While the issue requires further study, we speculate that differences in the washing and drying protocols applied to final precipitates may be one of the factors that have contributed to the discrepancies among published α-T curves.Owing to the rapid exchange of oxygen among the various hydrolytic Fe(III) species and ambient water, oxygen isotope equilibrium is probably attained between water and the ferric oxide gels and poorly-ordered ferrihydrite that are the initial precipitates in nearly all natural settings. Aging experiments suggest that isotopic compositions carried by ferric oxide gels and ferrihydrite are almost entirely erased by later exchange with ambient water during the maturation processes leading to formation of either hematite or goethite. These results suggest that dissolution and reprecipitation occur in the supposedly “solid-state transformation” from ferrihydrite to hematite. Thus the δ18O value of natural crystalline ferric oxides may provide a record of the long-term average δ18O value of local surface water, rather than that of the water from which the solid ferric oxide first formed.